Formulation Development and Evaluation of Bilayer Tablet for Effective Treatment of Gastric Ulcer - Rohit, Ajay; Patel, Mukesh Kumar; Manigauha, Ashish (Journal of Drug Delivery and Therapeutics, 2019)
The present study was aimed at developing Gastro retentive bilayer drug delivery systems containing esomeprazole and clarithromycin for the treatment of H. pylori induced gastric ulcer to minimize the side effect, improve the prolongation of action, to reduce the frequency of drug administration. The tablet is characterized by immediate release layer of esomeprazole and Gastroretentive layer of clarithromycin. The formulation containing Gastroretentive layer was designed using HPMC K 15, HPMC K4 and PVP K30 as floating agents, sodium bicarbonate and citric acid as gas-generating agent. Crospovidone, sodium starch glycolate and croscarmellose sodium was used as superdisintegrant for the preparation of immediate release layer. The prepared Gastroretentive layer was evaluated for their precompression parameters, physical characteristics like hardness, friability, uniformity of weight, uniformity of drug content, swelling index, In-vitro floating studies and In-vitro drug release. The release of the esomeprazole from the immediate release layer was found to be 89.98 % in 15minutes. The release of clarithromycin for the sustained release floating layer was found to be 98.89±0.47% in 12 hours. The data obtained from In-vitro release were fitted into the various kinetic models (Zero Order, Higuchi, First Order and Korsmeyer–Peppas Model).Keywords: Esomeprazole, Clarithromycin, Bilayer floating tab, Crospovidone, Superdisintegrant